Quality of life and perceived health status in adults with congenitally corrected transposition of the great arteries - Cotts, Timothy; Malviya, Sanjana; Goldberg, Caren (The Journal of thoracic and cardiovascular surgery, 2012)
The purpose of this study is to assess perceived health status and quality of life in adults with congenitally corrected transposition of the great arteries who have not undergone anatomic repair. Quality of life as measured by the satisfaction with life scale and linear analog scales and perceived health status as measured by the Short Form 36 Health Survey (version 1) were evaluated in 25 adults with congenitally corrected transposition and compared with a control group of 25 adults with mild, hemodynamically insignificant defects. Instruments were returned by 83% of patients (25/30; 11 male; mean age, 44.6 ± 16 years). Health status by the linear analog scale was significantly lower (P = .03) in subjects (median, 80; range, 15–100) than in controls (median, 85; range, 65–100). Quality of life by the satisfaction with life scale was also lower (P = .009) in subjects (mean, 24 ± 8) compared with controls. Age was negatively correlated with the Short Form 36 Health Survey physical functioning (r = −0.41, P = .04), bodily pain (r = −0.5, P = .01), and physical component (r = −0.56, P = .004) summary scores in adults with congenitally corrected transposition but not in controls. Adults with congenitally corrected transposition have lower reported health status and satisfaction with life than a control population, with perceived health status declining with advancing age.